Antiinflammatory Activity of Defatted Extract of Oleo Gum Resin of Boswellia serrata - KAUSHIK, NIRANJAN; SINGH, D.C.P.; MALIK, ANUJ; KUMAR, PRADEEP (Asian Journal of Chemistry, 2010)
Defatted alcoholic extract of the oleo gum resin of Boswellia serrata was screened for antiinflammatory activity in carrageenan induced rat paw edema at the dose level of 250 and 500 mg/kg and compared to the standard drug diclofenac sodium. The result were found to be significant (p < 0.001) when compared to the control.